MEMBANGUN SISTEM PELAYANAN KEPERAWATAN: SEBUAH WACANA (BUILDING A BETTER DELIVERY SYSTEM) - Supratman, Supratman (Universitas Muhammadiyah Surakarta, 2009)
Relatively little technical talent or material resources have been devoted to improving or optimizing the operations or measuring the quality and productivity of the overall health care system. One need only note that: (1) many patient in Indonesia die and also suffer injuries each year as a result of broken health care processes and system failures; (2) little more than half of patients receive known â€œbest practiceâ€ treatments for their illnesses and less than half of physician practices use recommended processes for care. Engineering tools and technologies that could help the health system overcome these crises and deliver care that is safe, effective, patient centered, timely, efficient, and equitable (SEPTEE). Systems engineering tools that have transformed the quality and productivity performance of other large-scale complex systems (e.g., telecommunications, transportation, and manufacturing systems) could also be used to improve health care delivery. Engineering applications with the potential to improve health care delivery in the short, medium, and long terms; and also to rapid improvements in the performance of the health care delivery system.